Analisis Faktor-Faktor yang Mempengaruhi Pergeseran Penggunaan Aplikasi Mobile Banking BSI ke Byond Studi Kasus Bank Syariah Indonesia KCP Tanjungbalai - Sitorus, Rahmadini; Maidalena, Maidalena (Universitas Syiah Kuala, 2025)
This study aims to analyze the factors influencing the shift in the use of mobile banking applications from BSI Mobile to BYOND by BSI, with a case study at BSI KCP Tanjungbalai. Using a descriptive qualitative approach through semi-structured interviews and direct observation, the findings reveal that the transition is driven by the need for more modern digital services, a more responsive user interface, and more comprehensive Sharia-compliant features, such as ZISWAF and Islamic financial consultations. Digital education and promotional strategies also supported the migration process. However, the transition did not proceed smoothly due to technical issues, limited digital literacy, resistance from long-time users, and a lack of direct assistance. These challenges indicate that the success of digital transformation depends not only on technological advancement but also on system readiness, effective communication, and continuous customer education. The study highlights the importance of consistent innovation and inclusive approaches to ensure that the digital transformation of Islamic banking is effectively embraced across all customer segments